KESESUAIAN RESEP PASIEN UMUM RAWAT JALAN POLI ANAK DAN POLI OBGYN DENGAN FORMULARIUM RSU X - Oviani, Gusti Ayu; Gayatri, Ni Putu Ayu Deviana; Yunita, Ella (Institut Teknologi dan Kesehatan Bintang Persada, 2025)
The appropriate and guideline-based use of medications is an important factor in providing optimal pharmaceutical care to outpatient patients in the Pediatric and Obstetrics and Gynecology clinics at X General Hospital. Therefore, it is necessary to conduct research to evaluate the suitability of prescriptions. This study aims to evaluate the suitability of outpatient prescriptions in the Pediatric and Obstetrics and Gynecology clinics with the Formulary of X General Hospital (X General Hospital Formulary). The research method used in this study was prospective observational research. The collected data were analyzed descriptively. The study was conducted at X General Hospital in April 2023. The sample of this study consisted of 69 prescriptions from the Pediatric clinic and 50 prescriptions from the Obstetrics and Gynecology clinic, which were selected using purposive sampling technique and met the inclusion criteria while not meeting the exclusion criteria. The results of the analysis showed that 88% of the prescriptions in the Obstetrics and Gynecology clinic and 88.41% of the prescriptions in the Pediatric clinic were in accordance with the X General Hospital Formulary. The suitability analysis based on drug items showed that approximately 91.43% of the drug items in the Obstetrics and Gynecology clinic and 93.24% of the drug items in the Pediatric clinic were in accordance with the X General Hospital Formulary. Some drug items that were not in accordance with the formulary in the Obstetrics and Gynecology clinic were Utrogestan, Folamil Genio, and Folac, as they had not been requested by the attending physician, while in the Pediatric clinic, Nasacort, FG Troches, Opicort, Prednicort, Ceftik, and Salbuven were not in accordance due to being rarely prescribed (death stock), rarely prescribed in patient therapy (slow moving), and not requested by the attending physician.